Recent developments in Lablab purpureus genomics: A focus on drought stress tolerance and use of genomic resources to develop stress‐resilient varieties. Issue 3 (9th June 2021) - Missanga, Julius S.; Venkataramana, Pavithravani B.; Ndakidemi, Patrick A.
Abstract: Drought is a major climatic challenge that contributes significantly to the decline of food productivity. One of the strategies to overcome this challenge is the use of drought‐tolerant crops with a wide range of benefits. Lablab is a leguminous crop that has been showing high promise to drought tolerance. It is reported to have higher drought resilience compared with the commonly cultivated legumes such as common beans and cowpeas. Because of its great genetic diversity, Lablab can withstand high temperature and low rainfall, unlike other related crops. On top of that, it is grown for multitudes of purposes including food, forages, conservation agriculture, and improved soil fertility. To enhance its production and benefits during the present effects of climate change, it is crucial to develop improved varieties that would overcome the challenge of drought stress. In the past years, there have been several reviews on Lablab based on origin, domestication, characterization, utilization, germplasm conservation, some cultivation constraints, and conventional breeding with limitations on the genomic exploitation of the crop for drought tolerance. Conventional breeding is the major breeding technique for many Lablab cultivars. The integration of genomic, physiological, biochemical, and molecular approaches would be required to develop drought‐tolerant cultivars of Lablab. In this review, we discuss recent developments in Lablab genomics with a focus on drought stress tolerance and the use of genomic resources to develop stress‐resilient varieties.